2020
DOI: 10.1088/1742-6596/1618/2/022040
|View full text |Cite
|
Sign up to set email alerts
|

Launch of the FarmConners Wind Farm Control benchmark for code comparison

Abstract: Careful validation of the modelling and control actions is of vital importance to build confidence in the value of coordinated wind farm control (WFC). The efficiency of flow models applied to WFC should be evaluated to provide reliable assessment of the performance of WFC. In order to achieve that, FarmConners launches a common benchmark for code comparison to demonstrate the potential benefits of WFC, such as increased power production and mitigation of loads. The benchmark builds on available data sets from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As a result, the technological approach for collaborated wind farm control is presently under advancement in multiple research institutions and industries. In particular, the FarmConners environment was introduced recently for the purpose of producing datasets as the basis for the evaluation of different control models in aiming to alleviate the barriers for wind farm control acceptance (Göcmen et al, 2020). In addition, the project was started by FarmConners to eliminate the challenges associated with the commercial application of wind farm control by collaborating a genuine assessment of the state-of-the-art of wind farm control in the FarmConners environment.…”
Section: Recent Challenges and Future Prospects Of Research Studies O...mentioning
confidence: 99%
“…As a result, the technological approach for collaborated wind farm control is presently under advancement in multiple research institutions and industries. In particular, the FarmConners environment was introduced recently for the purpose of producing datasets as the basis for the evaluation of different control models in aiming to alleviate the barriers for wind farm control acceptance (Göcmen et al, 2020). In addition, the project was started by FarmConners to eliminate the challenges associated with the commercial application of wind farm control by collaborating a genuine assessment of the state-of-the-art of wind farm control in the FarmConners environment.…”
Section: Recent Challenges and Future Prospects Of Research Studies O...mentioning
confidence: 99%
“… Quantification of the impact of wind farm control strategies on the wind turbine loads would be highly advantageous in moving wind farm control strategies forward towards widespread implementation and industry acceptance. Wind farm power maximisation is designed and evaluated on many different models, which makes the evaluation of the performance of different control approaches difficult. The FarmConners benchmark was launched recently to provide data sets on which control models can be evaluated [241]. While in simulations it was shown that the power production of wind farms can be increased with a cooperative control strategy, the proof‐of‐concept on a real wind farm is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…The FarmConners benchmark is launched in TORQUE 2020 (Göçmen et al, 2020a), and in the end, 13 participants have submitted the results from their models, taking part in different blind tests. The overview of participants among the benchmark blind tests is presented in Table 1, and it should be noted that some participants have provided results from several models.…”
Section: Introductionmentioning
confidence: 99%